2011
DOI: 10.2528/pier10082504
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Rate Probability Density Evaluation and Mapping for the Estimation of Rain Attenuation in South Africa and Surrounding Islands

Abstract: Abstract-The paper describes the modelling of the average rainfall rate distribution measured at different locations in South Africa. There are three major aspects this paper addresses: to develop a rainfall rate model based on the maximum likelihood method (ML); to develop contour maps based on rainfall rate at 0.01% percentage of exceedence; and re-classification of the ITU-R and Crane rain zones for the Southern Africa region. The work presented is based on fiveminute rainfall data converted to one-minute e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…As seen from Fig. 7, the classical PDFs contain Gauss, Rayleigh, Weibull and Logarithmic normal [32,33]. Table 1 shows that Gauss function has the minimum MSE with the distributions of feature 1 and feature 2.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from Fig. 7, the classical PDFs contain Gauss, Rayleigh, Weibull and Logarithmic normal [32,33]. Table 1 shows that Gauss function has the minimum MSE with the distributions of feature 1 and feature 2.…”
Section: Resultsmentioning
confidence: 99%
“…While Durban is subtropical, there is the immense maritime influence on its climate, hence the comparison of the Durban N (D) with distributions from tropical regions with strong maritime influence such as Singapore, Indonesia, East coast of Brazil, and Calcutta in India -sites for which a lot of work has been reported. However, we also note that South African climate is very varied, with Cape Town having a Mediterranean climate, while Pretoria has a temperate climate; hence when we look at these two cities later, their distributions will not be compared against those of tropical areas, but rather temperate and Mediterranean regions, as corroborated by Owolawi [28].…”
Section: Introductionmentioning
confidence: 88%
“…The conversion is unique to a particular region because it involves the geographical and climatic properties of a location. While notable methods of conversion have been developed [8,[10][11][12][13][14][15][16][17][18][19], it is interesting to note that some of these methods depend on the prevailing climatic factors. The rainfall rate conversion methods have been classified into three categories by Emiliani et al [20] namely: physical-stochastic, empirical and analytical methods.…”
Section: Integration Time Rainfall Rate Conversionmentioning
confidence: 99%
“…Many researchers [7,8] have suggested the use of integration times of 1-minute as the most suitable. Rainfall studies in Africa [4-7, 9, 10] and South African region [11][12][13] have suggested the need for adequate rainfall data at 1-minute integration time, which are scarce. However, higher integration time data (hourly, daily and even, monthly) are available from many weather stations.…”
Section: Introductionmentioning
confidence: 99%